AB0988 Inflammation in hand osteoarthritis remains constant after a period of 3 months. (23rd January 2014) - Kortekaas, M.; Kwok, W.Y.; Reijnierse, M.; Huizinga, T.W.; Kloppenburg, M.
Abstract : Background: Recent studies have shown that inflammatory ultrasound (US) features are frequently present in hand osteoarthritis (HOA) and are associated with pain on joint level. It is not known, however, how these features evolve over time. Objectives: To study the development of inflammatory features and pain over a 3 months period in HOA patients. Methods: In 25 consecutive HOA patients (mean age 60 years, 76% women) fullfilling the American College of Rheumatology (ACR)criteria, demographic characteristics and scores of Visual Analogue Scale (VAS) pain were collected at baseline and at 3 months. Pain was assessed by palpation of all 1st CMC, MCP, PIP, DIP and 1st IP joints. With ultrasound (US), grayscale (GS) synovitis and Power Doppler signal were scored in all hand joints using a standardized semi-quantitative scoring method (grade 0-3) by two observers (MCK, WYK). Associations between inflammatory US features and pain per joint were analyzed using Generalized Estimated Equations to account for patient effects with adjustments for age, sex, Body Mass Index (BMI). Results: Summated inflammatory US features did not change at 3 months; mean (range) GS synovitis 7.5 (0-16) at baseline versus 7.5 (0-18) at 3 months and PDS 3.0 (0-7) at baseline versus 2.0 (0-9) at 3 months. In 125 of 750 joints, GS synovitis was present at both baseline and 3 months, 62 joints showed GS synovitis at baseline only and 77 joints at 3 months only. Eleven of 750 joints showed PDS at both baseline and 3 months, 28 at baseline only, 16 at 3 months only. Overall pain decreased over 3 months time: median VAS pain (range) 49 (1-76) to 39 (1-76) mm; summated tenderjoints median (range) 8 (1-23) to 3 (0-16) respectively. Associations between inflammatory US signs and pain at palpation became stronger especially for GS synovitis: odds ratio (OR) 5.4 (1.9-15.6) and for PDS 3.6 (2.1-6.3) at baseline and OR 21.5 (3.5-117.3) and 4.1 (2.1-7.9) at 3 months, respectively. Conclusions: In HOA summated inflammatory US features are stable over time, but inflammatory US features on joint level are more variable. In the course of 3 months pain diminished, while the association between painful joints and inflammatory US features grew stronger. This emphasizes the multifactorial etiology of pain, which should be taken into account while studying clinical outcomes in HOA. Disclosure of Interest: None Declared